Aspergillus flavus Promoted the Growth of Soybean and Sunflower Seedlings at Elevated Temperature. (2nd May 2019) - Ismail; Hamayun, Muhammad; Hussain, Anwar; Afzal Khan, Sumera; Iqbal, Amjad; Lee, In-Jung
Abstract : The current climate changes in the form of global warming are one of the leading threats to agricultural crops (including soybean and sunflower). To enable the crops to cope with the heat stress, innovative steps are needed to be taken as soon as possible. Fungal endophytes are known to secrete secondary metabolites that promote the growth of host plants under stress conditions. Therefore, we have isolated endophytic fungus from Euphorbia indica (a wild desert plant) and tested it for plant growth promoting activities. The culture filtrate of the fungal strains exhibited the presence of secondary metabolites. Higher amounts of indole acetic acid (IAA), salicylic acid (SA), flavonoids, and phenolics have been found in the culture filtrate. The 18S rDNA sequence homology and phylogenetic analysis revealed that the isolate is Aspergillus flavus . Soybean and sunflower seedlings were inoculated with the identified A. flavus . The A. flavus -associated seedlings along with the control (without A. flavus ) were monitored for thermal stress resistance in a growth chamber, operated at 25°C and 40°C. Control seedlings exposed to high temperature stress had higher levels of abscisic acid (ABA), proline, and lower levels of phenols, flavonoids, catalase, and ascorbic acid oxidase. Similarly, a higher reduction in chlorophyll, root-shoot length, and dry weight has been noticed in the control seedlings. The results suggested the usefulness of A . flavus in host plant growth promotion under heat stress conditions.